Hybrid azole-based conjugates as upcoming anticancer and antimicrobial agents - Luís M. T. Frija; Bruno E. C. Guerreiro; Inês C. C. Costa; Vera M. S. Isca; Lucília Saraiva; Beatriz G. Neves; Mariana Magalhães; Célia Cabral; Maria L. S. Cristiano; Patrícia Rijo (Exploration of Drug Science)
Aim: This study discloses the synthesis and the antimicrobial and anticancer activities of four molecules of structural basis saccharin-thiadiazolyl (4), saccharin-pyridyl (6, 8), and tetrazole-thiadiazolyl (11). Methods: Antimicrobial properties of the molecules were evaluated by the well-diffusion method, against Gram-positive bacteria [Staphylococcus aureus American Type Culture Collection (ATCC) 25923, Staphylococcus epidermidis ATCC 12228, Mycobacterium smegmatis ATCC 607], Gram-negative bacteria (Pseudomonas aeruginosa ATCC 27853) and yeast (Saccharomyces cerevisiae ATCC 2601 and Candida albicans ATCC 10231) strains. The anticancer activity of the compounds was assessed through i) proliferation assays for HCT116, MCF-7, and A375 human cell lines [cells were treated with serial dilutions of compounds and the effect on cell propagation was evaluated by sulforhodamine B (SRB) assay]; ii) antiproliferative and cytotoxic assays for glioma-type cell lines A172 (glioblastoma), U87 (brain-likely glioblastoma), and H4 (neuroglioma; cells were treated with diverse concentrations and the cell viability was assessed using a modified Alamar blue® assay). Results: Compound 11 exhibited significant inhibitory activity against S. aureus and S. epidermidis, with the further molecules demonstrating some inhibitory potential against all the tested Gram-positive, Gram-negative, and yeast strains. Similarly, derivative 11 showed an interesting antiproliferative activity against human colon adenocarcinoma (HCT116), human breast adenocarcinoma (MCF-7), and melanoma (A375) cells, with 50% growth inhibition (GI50) values varying from 3.55 µmol/L to 11.5 µmol/L, in the same order of magnitude of those shown by etoposide. Treatment of brain-like glioblastoma cells (U87) with 11, at the concentration of 100 µg/mL, induced a decrease in cell viability by 50% after 48 h and 72 h. Besides, results attained for A172 cells have shown that compound 11 only induces a significant decrease in cell viability upon treatment at 100 µg/mL for 72 h. A divergent observation was recorded for H4 cells, where the treatment with derivative 11 had promoted a significant decrease in cell viability (< 40–60%), even at concentrations as low as 0.39 µg/mL, after 24 h. Conclusions: This investigation reveals the potential of distinct azole-based conjugates, in particular the tetrazole-thiadiazolyl (11) derivative, as scaffolds worth further investigations, in the frame of antimicrobial and antineoplastic chemotherapy.